Medicine falsification, organised crime and international cooperation (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
Counterfeiting of medicines is a threat to the whole international community and is deeply related to organised crime. The transnational dimension of this multifaceted phenomenon makes necessary to develop international instruments to tackle it. However, and notwithstanding the advancements on the notion of falsified medicines, there is not a common definition in the international legal instruments analyzed. Furthermore, the MEDICRIME Convention, although representing a remarkable step forward concerning criminal sanctions, has been ratified by few States and does not adequately take into account aspects related to the organized crime involvement. In this regard, the applicability of the UN Convention against Transnational Organized Crime to the falsification of medicines and the draft model law of UNODC on fraudulent medicines become relevant. Finally, the proposals to elaborate a broader international instrument within the WHO or the UNODC do not seem feasible in the short term, this also being a deep limit in the fight against falsified medicines.KEYWORDS: falsified medicines, transnational organised crime, intellectual property, MEDICRIME Convention, UN Convention against Transnational Organized Crime